EDIBLE LANDSCAPE INITIATIVE: A SUSTAINABILITY PROJECT - Harper, Grace Michelle; Mauzy, Heather; Coman, Jacob; Hurst, Jonathan; Patel, Ethan (East Carolina University, 2022)
Climate change is a wicked problem that is faced by every person on earth. Whether this impact comes in the form of food scarcity, weather changes, disease, or the destruction of homes and habitats makes no difference. While the climate does go through a series of changes and rotations, the changes that we are experiencing now are exponentially higher and thus more dangerous. Climate change has been fueled by an excess use of fossil fuels, an excessive amount of deforestation, and an excessive attitude of uncaring within large companies and governments that have the ability and power to create real change. This problem has only grown in the past years and will continue to grow unless a change is made within each citizen of the world. The Edible Landscape Initiative began as a group of honors college freshmen. Our passion for the environment brought us together to make an impact. The goal: is to create an orchard to bear fruit for the community, promote an ecocentric worldview, and spread the love of the environment across college campuses. By giving others the ability to invest in the environment through the establishment of orchards, we ensure future generations have effortless access, and the opportunity to cultivate a love for the natural world. The Edible Landscape Initiative group procured land, developed plans for the orchard (fruit trees, bushes, and pollinator/herb garden), gained necessary university approvals, and established ties with university communities to create a sustainability plan. Through crowdfunding, we raised approximately seven thousand dollars, developed service opportunities, and negotiated the purchase of all plants, soil, and tools (planted on April 24, 2021.) The success of this project stands as evidence that not only can students make a difference on their physical campus, but also in the mindset of those around them. In conclusion, the destruction that climate change causes will not be fixed with one change, but instead a change of mindset within a community is needed. One small orchard within a single community can help to inspire and grow an ecocentric mindset within areas around the community, country, and around the world. The Edible Landscape Initiative actively works to create a change within the world by creating a change within the minds of students who will go on to positively change the world.
Keywords: Environment; Orchard; Creative; climate change; sustainability; social impact project